sistem informasi pendaftaran ujian di fakultas keguruan dan ilmu pendidikan - sucipto, sucipto (INTEK : Jurnal Informatika dan Teknologi Informasi, 2021)
Based on research at the Faculty of Teacher Training and Education, Dehasen University found problems regarding the implementation of uncomputerized exam registration. This results in frequent errors when applying for exams, the absence of a database specifically for data storage that will be processed by lecturers and students at the Faculty of Teacher Training and Education, Dehasen University.In writing this Final Task the research method conducted is literature study research and interviews that are forwarded questions by going through question and answer with staff at the Faculty of Teacher Training and Education, Dehasen University. In utilizing this computerized system is expected to help the decision-making process and by utilizing the PHP programming language (Hypertext Processor) and codeIgniter framework as software that is expected in this application can replace the less efficient and effective way and can facilitate the creation of reports.